Selling British Columbia : tourism and consumer culture, 1890-1970 - Dawson, Michael, 1971- (UBC Press, 2004)
"Selling British Columbia examines the development of the tourist industry in British Columbia throughout the twentieth century. Looking at tourism from an innovative perspective, Michael Dawson shows how the province's Aboriginal and British cultures were commodified and marketed to potential tourists, and considers the gendered nature of some of the promotional campaigns, particularly during the 1940s." "Dawson's analysis draws on promotional pamphlets, newspaper advertisements, and films as well as archival sources about government, civic, and international tourism organizations. He argues that in order to understand the roots of the fully fledged consumer culture that developed in Canada, it is necessary to understand the connections between the 1930s, 1940s, and the postwar era. He underlines the significance of the Depression and the Second World War - ostensibly periods of "underconsumption"--For the development of tourism promotion and consumerism in general." "This cultural history will be welcomed by British Columbian and Canadian historians, as well as scholars of consumer culture and tourism."--Jacket